2015
DOI: 10.1016/j.proenv.2015.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Active Acid Catalyst of Sulphated Zinc Oxide for Transesterification of Soybean Oil with Methanol to Biodiesel

Abstract: Active solid acid catalysts of sulphated zinc oxide (SO 4 2--ZnO and SO 4 2-/ZnO) were prepared and characterized. The solid acid catalysts were investigated for their performance on transesterification of soybean oil with methanol to produce biodiesel. The SO 4 2--ZnO and SO 4 2-/ZnO catalysts were prepared by coprecipitation and impregnation respectively to compare their performance for biodiesel production. The catalysts were characterized by X-ray Diffraction (XRD) and Fourier Transform Infra Red (FT-IR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…The optimum catalyst loading amount was found to be 10.0% in this system and the methyl ester yield reaches of 88.6 wt.% during 3 h. Loading catalyst is very effecting to increase catalytic activity at certain condition. If the amount is in the right portion then the production can be maximize [30][31][32]. The burning process of the coconut husk play an important role in forming an active component of the catalyst.…”
Section: Effect Of Catalyst Loading On Biodiesel Yieldmentioning
confidence: 99%
“…The optimum catalyst loading amount was found to be 10.0% in this system and the methyl ester yield reaches of 88.6 wt.% during 3 h. Loading catalyst is very effecting to increase catalytic activity at certain condition. If the amount is in the right portion then the production can be maximize [30][31][32]. The burning process of the coconut husk play an important role in forming an active component of the catalyst.…”
Section: Effect Of Catalyst Loading On Biodiesel Yieldmentioning
confidence: 99%
“…In this context, mixed oxides, other mixed compounds (Jindapon et al, 2016), sulfated oxides (Istadi et al, 2015), zincates (Rubio-Caballero et al, 2009), and magnetic catalysts (Dantas et al, 2017) have been reported for the processing of vegetable oils and animal fats with low acid contents (Dias et al, 2012;Pasupulety et al, 2015). Other authors employed solid catalysts for the processing of raw materials with high FFA contents, such as sulfonated solids, used in reactions with materials containing FFA contents of 10 % (Fadhil et al, 2016), 15 % (Dawodu et al, 2014) and up to 43.73 % (Konwar et al, 2014), and bifunctional catalysts with both Brönsted and Lewis acid sites, used for the processing of materials with FFA contents of 1.78 % (Pan et al, 2018) and from 8.6 % to 60 % (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most commercial processes used for biodiesel synthesis employ a homogeneous base catalyst, such as NaOH or KOH. However, it suffers several drawbacks, such as equipment corrosion and deal with H 2 SO 4 waste produced from neutralization process [10,11]. This situation has deficiency not only due to high catalyst consumption but also biodiesel purification process would be difficult.…”
Section: Introductionmentioning
confidence: 99%